The European Code of Cancer Practice. (June 2021) - Lawler, Mark; Oliver, Kathy; Gijssels, Stefan; Aapro, Matti; Abolina, Agnese; Albreht, Tit; Erdem, Sema; Geissler, Jan; Jassem, Jacek; Karjalainen, Sakari; La Vecchia, Carlo; Lievens, Yolande; et al.
Graphical abstract: Highlights: The Code is a citizen and patient-centred accessible statement of the core requirements for good clinical cancer practice. The Code has 10 key overarching Rights of what a patient should expect from their healthcare system, supported by a plain language explanation. The Code has been co-produced to bridge the gap between clinical guidelines, healthcare policies and patients' everyday experience. The Code is robustly evidence-based and supported by a comprehensive review of the medical literature and evidence. The Code is strongly endorsed by Europe's professional and patient cancer organisations and the European Commission. Abstract: There are considerable disparities between the quality of cancer care and clinical outcomes for cancer patients in different European countries, regions, hospitals and communities. These have persisted despite the introduction of many European and National Cancer Plans, an extensive portfolio of clinical guidelines and the existence of evidence based guidelines for the good practice in planning cancer healthcare systems. We describe the European Code of Cancer Practice which is a citizen and patient-centred accessible widely disseminated statement of the core requirements for good clinical cancer practice. The Code sets out 10 key overarching Rights of what a patient should expect from their healthcare system each supported by a plain language explanation. The Rights highlight the importance of equal access to affordable and optimal cancer care, good quality information about an individual patient's disease and treatment and about the quality and outcomes of the cancer service they will use. Specialised multidisciplinary cancer care teams, shared decision-making, research and innovation, a focus on quality of life, the integration of supportive and palliative care within oncology are all emphasised. There is a need for a systematic approach to supporting cancer survivors with a survivorship care plan including their rehabilitation, reintegration into society and return to work where appropriate without discrimination. The Code has been co-produced by a team of cancer patients, patient advocates and cancer professionals to bridge the gap between clinical guidelines, healthcare policies and patients' everyday experience. It is robustly evidence-based and supported by a comprehensive review of the medical literature and evidence for good clinical practice. The Code is strongly endorsed by Europe's professional and patient cancer organisations and the European Commission.